ADVERTISMENT IN ENGLISH AND UZBEK LANGUAGES - Pakirdinnova Sharofat Abdumutalovna; Bozorboyeva Khusnidakhan Bahromjon kizi (Journal of new century innovations, 2023)
The discussion of two forms of linguistic diversity found in Uzbek and English advertising discourse is presented in this paper. The study's data came from a variety of free media sources, and some of the observations were corroborated by sociolinguistic experimental techniques. According to others, the Uzbek advertising discourse is "creolizing," or absorbing features from other linguistic systems with which it interacts on the global market scene. All linguistic levels, from lexis and visuals to pronunciation and grammar, are involved in the creolization process, which is generally viewed favorably by native Uzbek speakers. The English (British) advertising discourse is shown to avoid language mixing, but to rely instead on the regional and social variation of English and to make use of non-standard language forms, especially in the pronunciation domain.